A Simplified Control Approach of AC-DC-TLBC for Bi-Polar DC Microgrid Applications - et. al., D. Sathisha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper the main focus is to convert 3-Phase AC to DC and DC to 3-level Boost conversion for bipolar DC micro grid applications. The input side of AC-DC converter acts as active PWM rectifier and this can be controlled by using a new Min Max (MM) control algorithm to maintain the regulated DC link voltage. The DC link voltage is boosted according to the duty cycle along with voltage balance compensation algorithm in 3-L Boost (TLBC) converter. Hence the combination of two control approaches can provide better dynamic and steady state responses and the output results are carried out by MATLAB /Simulink environment.